(X+30)(X-1)=0

Simple and best practice solution for (X+30)(X-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X+30)(X-1)=0 equation:


Simplifying
(X + 30)(X + -1) = 0

Reorder the terms:
(30 + X)(X + -1) = 0

Reorder the terms:
(30 + X)(-1 + X) = 0

Multiply (30 + X) * (-1 + X)
(30(-1 + X) + X(-1 + X)) = 0
((-1 * 30 + X * 30) + X(-1 + X)) = 0
((-30 + 30X) + X(-1 + X)) = 0
(-30 + 30X + (-1 * X + X * X)) = 0
(-30 + 30X + (-1X + X2)) = 0

Combine like terms: 30X + -1X = 29X
(-30 + 29X + X2) = 0

Solving
-30 + 29X + X2 = 0

Solving for variable 'X'.

Factor a trinomial.
(-30 + -1X)(1 + -1X) = 0

Subproblem 1

Set the factor '(-30 + -1X)' equal to zero and attempt to solve: Simplifying -30 + -1X = 0 Solving -30 + -1X = 0 Move all terms containing X to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + -1X = 0 + 30 Combine like terms: -30 + 30 = 0 0 + -1X = 0 + 30 -1X = 0 + 30 Combine like terms: 0 + 30 = 30 -1X = 30 Divide each side by '-1'. X = -30 Simplifying X = -30

Subproblem 2

Set the factor '(1 + -1X)' equal to zero and attempt to solve: Simplifying 1 + -1X = 0 Solving 1 + -1X = 0 Move all terms containing X to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1X = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1X = 0 + -1 -1X = 0 + -1 Combine like terms: 0 + -1 = -1 -1X = -1 Divide each side by '-1'. X = 1 Simplifying X = 1

Solution

X = {-30, 1}

See similar equations:

| -[6x-(2x+6)]=-1-[6(2x-4)-6x] | | 4a=12+a | | log(4x^2+5x)=log(34x+63) | | 9(6z-7)= | | (6p/2p-1)-3=3/p | | 3x^2-22x+40=0 | | 3a-1+4a+3= | | 9n-7= | | y/-2=-6 | | 6+3c=8+11c | | (X+36)(X-1)=0 | | (4+3i)(4-i)=0 | | (9)(-8)= | | 0.80x+0.70(20)=0.40(105) | | 8p+7=5p+7 | | a/-9=-35 | | 15+5=c+5c-2c | | (X+6)(X+5)=0 | | m/-76 | | -2(x-6)+3=15 | | (x-3)(x+4)=xsquared+12 | | 13-x+100-(-33)=99 | | (12/n+1)+1=12/n | | -45=-3y | | (X+18)(X+2)=0 | | 41-16=5(x-3) | | 5b+6b-17= | | (X+12)(X+3)=0 | | -[9z-(18z+3)]=3+(8z+7) | | B+3.25=5 | | 2(x+3)+3(2x-1)=40 | | 5x-12=3x+20 |

Equations solver categories